Control and integration of energy storage systems for electric and hybrid ships – part ii - Quek, Jun Hong (2017)
This final year report shows 2 different load profile from the ferry and coastal vessel where the author will introduce various generation logic implemented with the ESS to find out the more efficient way of the logics from the suggested .